The effect of using electronic software in increasing the achievement of ninth grade students in geography - Al- Maaytah, Wael Salama Abdulsamad (Journal of Educational and Psychological Sciences, 2020)
The present study aimed to identify the effect of using electronic software in increasing the achievement of ninth grade students in geography. The study adopted the experimental method. The tool consisted in (achievement test in geography), prepared by the researcher, it was applied to a random sample of two divisions of the class students. The ninth primary school in Abu Ayyub Al- Ansari Elementary School for Boys, affiliated to the Directorate of Education of the Governorate of Aqaba during the academic year 2018/2019, for Division (B) as an experimental group, consisting of (20) students, and Division (A) as a control group, and consisted of (20) students. The results of (T) test showed that there were statistically significant differences between the average scores of the students on the achievement test due to the variable of teaching method, where the control officer obtained a total average (25.80) in exchange for the pilot obtained a total average (36.02), and for the benefit of the experimental group, and in the light of the results Study The researcher recommended the training of teachers on electronic software in the teaching of geography.